Biochemical transformation of petroleum hydrocarbons in the waters of West Siberia - Panicheva, L. P.; Moiseyenko, T. I.; Kremleva, T. A.; Volkova, S. S.; Паничева, Л. П.; Моисеенко, Т, И.; Кремлева, Т. А.; Волкова, С. С. (Tyumen State University, 2012)
A study of the processes of biochemical transformation of petroleum hydrocarbons and nitrates in the waters of 127 lakes (from the tundra zone to the forest-steppe zone) in Western Siberia (ZS) was conducted. The main anthropogenic sources of pollution with petroleum products and nitrates are the exploitation of oil and gas fields and the burning of associated gas. For most of the lakes of the ZS, which are sufficiently remote from sources of anthropogenic pollution, the self-cleaning ability of reservoirs during the summer period ensures a decrease in the content of petroleum products and nitrates to values below the MPC for fishery reservoirs. At the same time, the content of organic carbon (Sorg) and organic nitrogen (Norg) increases significantly. For natural areas of the ZS, the median value of Sorg varies from 4.38 to 26.6 mg/dm3, Norg – from 0.17 to 1.52 mg/dm3. The biochemical transformation of petroleum products includes an anaerobic humification process and an aerobic mineralization process. In lakes of the northern and middle latitudes of the North (above latitude 58o), humification is 80%, mineralization is 20%; in lakes of the southern latitudes of the South (below latitude 58o), humification is 30%, mineralization is 70%. The anaerobic oxidation of hydrocarbons and organic residues is accompanied by the reduction of nitrates to nitrites and ammonium. Amination of intermediate products of oxidation of organic compounds leads to an increase in the content of organic nitrogen and humic substances. In the natural zones of the range of northern and middle latitudes (tundra, forest tundra, northern taiga, middle taiga), the waters of lakes contain a significant amount of ammonium, which determines the dominance of the humification process over the mineralization of organic matter. In the natural zones of the southern latitude range (southern taiga, forest steppe), the process of humification is limited by almost complete depletion of ammonium. The molar ratio of carbon and nitrogen in aqueous humic ...